Growth and production of seagrass Cymodocea serrulata (R.Br.) aschers et magnus and thalassia hemprichii (ehrenb.) aschers in Port Dickson, Negeri Sembilan, Malaysia - Mustafa Kamal, Abu Hena (2000)
Seagrass is one of the valuable components which contribute significantly in coastal productivity and stabilizing sea floor sediments in the shallow marine water ecosystems. Investigation on the shoot density, biomass, leaf growth, leaf production and habitat of two seagrasses, Cymodocea serrulata and Thalassia hemprichii, in a sparse, mixed stand and monospecific patches of Batu Tujuh, Port Dickson coastal area Negeri Sembilan, Malaysia are reported. Shoot density and biomass of these species was detected by placing 20 x 20 cm quadrat. Leaf growth and production was detected by leaf marking method. The mean shoot density was 950 ± 136.42 shootslm2 and 632.14 ± 113.77 shoots/m2 for C. serrulata and T. hemprichii, respectively. Above ground biomass of T. hemprichiiwas lower (13.878 ± 1.173 g AFDW/m2) when compared to those of C. serrulata (20.250 ± 4.053 g AFDW/m2). The mean leaf growth of C. serrulata was higher (7.66 mm/shoot/day) compare to T. hemprichii (7.04 ± 1.35 mm/shoot/day). The present study indicates that the seagrass C. serrulata and T. hemprichii contributes a countable portion (0.961 ± 0.227 g AFDW/m2/day for C. serrulata and 0.563 ± 0.172 g AFDW/m2/day for T. hemprichil) of organic matter, together with phytoplankton and macro algae, to the total primary production in Port Dickson marine water. Relative production rates (RPR) was 0.057 ± 0.014 gig AFOW/day for C. serrulata ant1 0.058 gig OW/day for T. hemprichii. This result indicated that T. hemprichii produce more organic matter daily than C. serrulata in this marine area. The plastochrone interval of C. serrulata leaves was higher (14.74 ± 1.89 days) than T. hemprichii (12.03 ± 1.01 days), whereas, short plastochrone interval of leaves (PIL) allows a faster plant response than the long PIL. Dissolved oxygen and pH value of seawater of Batu Tujuh seagrass bed ranged between 7.8 - 8.8 mgll and 8.0 - 8.5, respectively. The range of salinity and light intensity were 24.0-30.0 ppt and 25.0- 1805.2 IJmoVm2/s, respectively. Concentrations of nutrients were greater in pore water than overlying seawater of this seagrass bed. Total nitrogen content of plant tissue varied between 0.349 ± 0.024 and 1.110 ± 0. 067% of OW in C. serrulata and 0. 195 ± 0.036 - 1.586 ± 0.041 % of OW in T. hemprichii. Total phosphorus was highest in leaves (0.276 ± 0.022 - 0. 377 ± 0. 034% of OW), intermediate values in rhizomes (0.157 ± 0.004 - 0.196 ± 0.021 % of OW) and lowest in roots (0.100 ± 0.004 - 0. 114 ± 0.003% of OW). Potassium content was relatively higher in C. serrulata leaves (2.267 ± 0.058% of OW) and roots (2.20 ± 0.50% of OW) in T. hemprichii. In situ photosynthesis varied at different depths. The highest rate of photosynthesis of both species was higher at 0.5 m depth than at 2. 0 m and this could be attributed to relatively higher light intensity at depth of 0.5 m. The respiration rate remained uniform at different depths for both species. Experimental photosynthesis study showed that the light saturation was reached at 200 - 800 and 400-800 µmol/m²/s for C. serrulata and T. hemprichii, respectively. The compensation light intensity was 20 - 40 µmol/m²/s for C. serrulata and around 20 µmol/m²/s for T. hemprichii. Comparing these results to in situ light measurements from the seagrass bed, it may be assumed that both seagrasses could penetrate deeper area in this seagrass bed. However, the photosynthesis produced at light intensity below 2.0 m depth «108.33 ± 9.177 µmol/m²/s for C. serrulata and <115 ± 1.512 µmol/m²/s for T. hemprichil) probably could not support the requirement during dark period, albeit lower light compensation (20-40 µmol/m²/s for C. serrulata and ± 20 µmol/m²/s for T. hemprichil) showed in the experimental study.